Moral Compass - Steel, Danielle (New York : Delacorte Press, 2020)
"Saint Ambrose Prep is a place where the wealthy send their children for the best possible education, with teachers and administrators from the Ivy League, and graduates who become future lawyers, politicians, filmmakers, and CEOs. Traditionally a boys-only school, Saint Ambrose has just enrolled one hundred and forty female students for the first time. Even though most of the kids on the campus have all the privilege in the world, some are struggling, wounded by their parents bitter divorces, dealing with insecurity and loneliness. In such a heightened environment, even the smallest spark can become a raging fire. One day after the schools annual Halloween event, a student lies in the hospital, her system poisoned by dangerous levels of alcohol. Everyone in this sheltered community--parents, teachers, students, police, and the media--are left trying to figure out what actually happened. Only the handful of students who were there when she was attacked truly know the answers and they have vowed to keep one anothers secrets. As details from the evening emerge, powerful families are forced to hire attorneys and less powerful families watch helplessly. Parents marriages are jeopardized, and students futures are impacted. No one at Saint Ambrose can escape the fallout of a life-altering event"--Provided by publisher.
Keywords: Preparatory school students -- Fiction; Preparatory schools -- Fiction; Private schools -- Fiction; Students -- Conduct of life; Fiction; Alcohol -- Toxicology; Fiction; Children of the rich -- Fiction; Rich people -- Fiction; Rape -- Investigation; Fiction; Truthfulness and falsehood -- Fiction; Secrecy -- Fiction; Life change events -- Fiction; Massachusetts -- Fiction; Bildungsromans